2009
DOI: 10.1038/ajh.2009.5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Long-Term Mortality in Patients With Type B Acute Aortic Dissection

Abstract: Impaired renal function was a predictor for adverse outcome in patients with type B AAD. The use of CCBs as antihypertensive medication at discharge was associated with increased survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Earlier studies have identified long‐term predictors of morbidity and mortality in AAD, including old age,13, 14 female sex,15 a history of atherosclerosis,4 and impaired renal function,16 all of which may be more representative of a patient's high‐risk clinical background than the severity and nature of the AAD itself. Indeed, as of yet, there may be no effective and simple marker available for evaluating severity of AAD, predicting long‐term clinical outcomes, and optimizing surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have identified long‐term predictors of morbidity and mortality in AAD, including old age,13, 14 female sex,15 a history of atherosclerosis,4 and impaired renal function,16 all of which may be more representative of a patient's high‐risk clinical background than the severity and nature of the AAD itself. Indeed, as of yet, there may be no effective and simple marker available for evaluating severity of AAD, predicting long‐term clinical outcomes, and optimizing surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…3,19,20,22 In particular, multiple groups have reported that the maximum aortic diameter (Ն40 mm) and false lumen closure status are long-term predictors in type B AAD. 4,6 -9 Some of these predictors, including sex, history of previous aneurysm, and history of atherosclerosis, may be more representative of a patient's high-risk clinical background rather than the nature of the aortic dissection itself.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic dissection is a life-threatening disease with high inhospital mortality [1][2][3][4][5]. Although hypertension, age, and atherosclerosis have been known to be risk factors of aortic dissection [6], other factors associated with aortic dissection were not sufficiently elucidated.…”
Section: Introductionmentioning
confidence: 99%